Transmission Performance Analysis of Slotted-type Eddy-current Couplers with Radial Misalignment - Yang Chaojun; Zhu Jiwei; Ding Lei; Hang Tian; Ding Yifei; Wang Jian (Jixie chuandong)
In order to study the transmission performance of slotted-type eddy-current couplers with radial misalignment, based on the theory of the equivalent magnetic charge theory, the copper which cuts the magnetic field line in motion is equivalent to permanent magnet. Combining with Coulomb's law, a calculation model of output torque is established in this study. The analysis of magnetic flux density, copper loss and output torque of couplers are all simulated by finite element software, and the maximum allowable value of radial misalignment is obtained. The results show that with the increase of radial misalignment, the induced magnetic field decreases during operation, which results in the increase of the magnetic flux density, the decrease of the copper loss and the torque, and the fluctuations of the copper loss and the output torque changing with time become more and more obvious. When the radial misalignment is less than 6 mm, the torque generated by the couplers can almost be remained accurately and the fluctuation of the torque is relatively stable.